Effects of Core Muscle Acupuncture on Trunk Stability Control in Children with Spastic Cerebral Palsy - Jie ZHANG; Qing HUANG; Shibin LI; Suqiao CHEN; Wenfang DING; Dong LIN (康复学报)
Objective:To investigate the effects of core muscle acupuncture on the trunk stability control in children with spastic cerebral palsy.Methods:Thirty cases of spastic cerebral palsy children with sitting disequilibrium were selected and divided into equal two groups by simple randomization. The patients of rehabilitation group were taken regular rehabilitation protocol for sitting disequilibrium, while the patients of acupuncture group were taken core muscle acupuncture combined with the same regular rehabilitation protocol mentioned above. The Pro-kin 254 equilibrium training detector was applied to detect the scores of the trunk control ability after six months therapeutic course, along with those in sitting position (region B) among the 88 items in the gross motor function measure (GMFM-88).Results:1) All indicators of trunk stability control in the acupuncture group were superior after treatment compared to those before treatment (P<0.05); the swinging path length of the center of gravity in the rehabilitation group were better after treatment than that before treatment (P<0.05);and the differences in the deviations of the center of pressure (COP) in the anterior-posterior and left-right directions, the average speeds of movement in the anterior-posterior and left-right directions, along with the ellipse area formed by the shifting of the center of gravity before and after treatment in the acupuncture group were superior to those in the rehabilitation group (P<0.05).2) The GMFM-88 scores in sitting position in both groups were better after treatment than those before (P<0.05);and the differences in the GMFM-88 scores in sitting position before and after treatment were better in the acupuncture group than that in the rehabilitation group (P<0.05).Conclusion:Core muscle acupuncture could improve the trunk control in sitting position in children with spastic cerebral palsy; in addition, the introduction of the sport medicine theories into the acupuncture treatment would exploit a new thought for acupuncture site selection in improving the dyskinesia in children with spastic cerebral palsy.